Relationship between Clinicopathologic Features and Recurrence in Ovarian Germ Cell Tumor - Mozhdeh Momtahan; Mojgan Akbarzadeh-Jahromi; Saeid Jokar; Shaghayegh Moradi-Alamdarloo; Fatemeh Sari Aslani; Maryam Rohani (Middle East journal of cancer, 2021)
Background: We conducted the present study to analyze the clinicopathologic features of patients with malignant ovarian germ cell tumor (MOGCT) with recurrence after 2 and 5 years. Method: In this retrospective and analytical-descriptive study, the obtained data included: age, tumor size, histopathological type, tumor stage, lymph node involvement, laterality of tumor, tumor necrosis, and mitosis. We also evaluated the Cox Regression analysis between these variables with recurrence after 2 and 5 years. Results: According to our exclusion criteria, we eliminated 81 cases. These cases consisted of the subjects with dysgerminoma (48.1%), immature teratoma (22.2%), yolk sac (16%), mix germ cell (11.1%), non-gestational choriocarcinoma (1.2%), and embryonal carcinoma (1.2%). We did not observe pure polyembryoma or polyembryoma in combination with mixed germ cell. All the patients received the treatment. The patients’ mean age was 23.3±8.4 years. MOGCT reoccurred in 10 patients after 2 years and in 13 patients after 5 years (10 cases in the first 2 years, and 3 new cases in the next 3 years). Most of the cases (64.2%) were diagnosed to be at stage 1. The Cox regression analysis between positive lymph node and the recurrence of MOGCT after 2 years and between stage IV of disease and the recurrence after 2 years were significant. The Cox regression analysis between laterality, mitosis and necrosis in pathologic slides of the recurrence after 2 and 5 years was not significant. Conclusion: Stages and involvement of lymph nodes are two major factors concerning the recurrence of MOGCT. Most recurrences occur in the first 2 years. Pathologic features (mitosis and necrosis) of MOGCt in the time of diagnosis not correlated with the recurrence of the disease.